Jurisdictional Synergy and Contradictions: Religious and State Courts in Indonesia's Pluralistic Inheritance Disputes - Ade Fariz Fahrullah; Nurhayati Zein; Muhammad Hafis; Juliani Syafitri; Wahyu Kurniawan (Fiat Justisia: Jurnal Ilmu Hukum, 2026)
Legal pluralism in Indonesia’s inheritance law, encompassing Islamic law, customary law, and the Civil Code, creates institutional dualism in dispute resolution. This article analyzes the roles of the Religious Court and District Court, identifies jurisdictional synergies and conflicts, and evaluates their implications for legal certainty and substantive justice using a normative juridical method supported by regulations, jurisprudence, and secondary data. The findings show that the Religious Court plays a central role, particularly in post-mortem marital property disputes and cases prone to forum shopping, while synergy appears in the execution of decisions through notaries and Land Deed Officials (PPAT) linking judicial determinations with land administration. Contradictions arise when such disputes are brought before the District Court, creating inefficient multi-stage processes and prolonging resolution, which weakens legal certainty and procedural efficiency. The study underscores the need for clearer regulatory alignment through Supreme Court instruments to define jurisdictional limits and prevent forum shopping, alongside strengthening judicial capacity and harmonizing the role of notaries and PPAT to achieve a more integrated and reliable system of inheritance dispute resolution.